The Truong Son, Loei-Phetchabun, and Kontum Terranes in Indochina: Provenance, Rifting, and Collisions - Burrett, Clive; Udchachon, Mongkol; Thassanapak, Hathaithip (Frontiers in Earth Science, 2021)
The three main regions of Indochina are defined as the Truong Son, Loei-Phetchabun, and Kontum terranes. The aim of this review is to integrate numerous petrological studies with sedimentary, palaeontological, and provenance studies in order to construct a preliminary tectonic model which shows the terranes docked in the earliest Carboniferous (Truong Son with Loei-Phetchabun) and in the Permian (Kontum). The Kontum Terrane is characterized by Proterozoic magmatism, mid-Ordovician to Early Devonian granites, and Permian charnockites. Major carbonate platforms developed in the Givetian to earliest Tournaisian on Truong Son and from the Visean to mid-Permian across Truong Son and Loei-Phetchabun terranes. The Truong Son has Silurian granites and a Late Ordovician to Silurian magmatic arc along its southern and western borders caused by subduction of oceanic lithosphere, the remnants of which are now partially preserved in the Loei and Tamky sutures. A region to the east of the Loei Suture in the Loei Foldbelt has a similar-age volcanic arc extending northwards into Laos and is included in Truong Son. A platform-margin coral-stromatoporoid reef developed on Truong Son in the Frasnian and was coincident with a gap in magmatism until the Pennsylvanian with granite magmatism became widespread until the Late Triassic. In the Loei-Phetchabun Terrane, Devonian siliciclastics, volcanics are overlain by Givetian limestones and patch reefs and in turn overlain by Late Devonian to earliest Tournaisian radiolarian cherts and siliciclastics. Tournaisian to early Visean siliciclastic turbidites were coincidental with initial uplift and deformation and were replaced by Visean terrestrial evaporites and coal and marine limestones. Arc magmatism along the Loei-Phetchabun Terrane indicates intermittent eastward subduction from mid-Devonian to mid-Triassic. Carboniferous-Triassic volcanism extends eastward along the northern margin of Cambodia and is probably an extension of Loei-Phetchabun. Ordovician within-plate basalts in Kontum and the transition from shallow marine Ordovician siliciclastics to Silurian deep-marine sediments and a volcanic arc in Truong Son suggest rifting of both terranes from Gondwana in the Late Ordovician. Initial docking of Truong Son with South China was probably in the late Silurian to Early Devonian and docking of Loei-Phetchabun and Truong Son was in the late Tournaisian to early Visean.